The Relationship Of Physical Activities And Adherence To Take Antidiabetic Drugs Toward Blood Glucose Levels On Type 2 Diabetes Mellitus - Pebriani, Sintiya Halisya; Astuti, Lenny; Pratiwi, Innes Hardi (Universitas Islam Lamongan, 2020)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia. Unable to control blood levels in patient with DM Type 2 can cause short-term, long-term complications and even death. Therefore, it must be agreed about the implementation of physical activity and adherence for taking medication. The aim of this study was to determine the correlation of physical activities and adherence to take antidiabetic drugs toward blood glucose levels on type 2 diabetes mellitus patient. The method of this research was an observational analytic study with a cross sectional design.The sample of the reserach was 40 patient with random sampling technique. The technique to convey was by glucometer and interview used a questionnaire. Analysis the data used the correlation kendallâ€™s tau test. The result of research showed that there was the positive correlation (p= 0,000 r = 0,529) between physical activity and blood glucose, and there was negative correlation (p= 0,002 r = -0,475) between adherence to take antidiabetic drugs with blood glucose.Â Â From the result of the analysis concluded that there was a posistive influence of physical activity ang blood glucose. Its was not related with existing theorise, but from the 25 respondents who had severe physical activity the were 20 respondents who were not compliant in consuming diabetic drugs, so there were negative correlation between adherence and diabetic blodd glucose.